Rumours and prophecies: the religious background of the late Yuan rebellions - ter Haar, Barend (Studies in Chinese Religions, 2018)
The conventional view of the late Yuan rebellions of Xu Shouhui and Han Shantong is that they were both inspired by Maitreyist beliefs. Han Shantong claimed that a Luminous King would appear. The prominent Chinese historian Wu Han therefore argued that this rebellion was influenced by Manichaean beliefs. The rebellion is also traditionally seen as the moment that the lay Buddhist devotionalist White Lotus movement worshipping Guanyin and Amitāhba changed into the messianic and supposedly rebellious White Lotus Teachings. I will demonstrate that the Xu Shouhui rebellion was not Maitreyist at all, but advocated the reestablishment of a Song dynasty. It included a large number of leaders with a background in the lay Buddhist White Lotus movement, but was never labelled a messianic White Lotus Teachings until modern historians applied this label. The Han Shantong rebellion on the other hand was definitively Maitreyist, but the belief in a Luminous King did not derive from Manichaean beliefs but from an old indigenous tradition, the Sutra of the Five Lords. I argue that even the choice of the name Ming for Zhu Yuanzhang’s new dynasty and his choice of the capital of Nanjing were inspired by this particular religious text.